Economic Participation among Older People - Catherine Aquiline Manda; Narathius Asingwire; David Mafigiri; Randi Kroken; Joyce Nyoni (Journal of Comparative Social Work, 2025)
Economic participation studies often emphasize challenges of accessing and engaging in formal employment after retirement. However, they tend to overlook personal factors, traditional values, and culturally specific elements in rural settings that influence participation in informal work. This study explored the factors that influence older people’s participation in handcraft activities in the Masasi District in Tanzania. It provides a deeper insight into their continued engagement, and highlights its implications for social work practice.